Alterations in Breast Tissue Morphology and Androgen Receptor Expression Following Masculinizing Gender-Affirming Hormone Therapy in Transgender Men - Poonpissamai Suwajo; Thawin Techapongsatorn; Adiluck Pisutpunya; Kasama Nilprapha; Jiraroch Meevassana; Apichai Angspatt; Kroonpong Iampenkhae; Saranpong Pornsinsirirak (Transgender Health, 2026)
Purpose: This study aimed to evaluate histological alterations and androgen receptor (AR) expression within breast tissue associated with masculinizing gender-affirming hormone therapy (GAHT) exposure of different duration in transgender men. Methods: A retrospective review of breast histopathological specimens obtained from 81 transgender men following gender-affirming mastectomy between 2017 and 2023 was conducted. Histological features and AR expression were compared between individuals with and without prior GAHT exposure, as well as between short-term (